"Hey Mom, I Missed School Today to Save the Planet!": Mandatory Attendance and Student Activism—A Canadian Perspective. Issue 1 (January 2022) - Clarke, Paul T.; Anderson, Mark; Yoh, Abdoulaye
In recent times, climate change has become an increasingly significant and pressing issue of ethical, social, political, economic, and environmental concern. Although mandatory attendance laws are important, we argue in the Canadian context that it is possible and indeed necessary to support an educational agenda that takes social activism seriously as a means to promote community, solidarity, concern for the environment, and global stewardship. We draw on the work of Rob Reich (2002) who claims that the state, parents, and children all have a stake in children's education, and include a fourth actor, namely teachers, who also have specific interests in children's education.